Mental Health Protection and Health Policy Towards People with Mental Illnesses. the Case of Poland - Dobrowolska, Małgorzata; Izydorczyk, Bernadetta (European Journal of Multidisciplinary Studies, 2016)
The aim of the article is to present basic data on the health policy in Poland for the years 2016-2020 in the context of current standards and developmental goals for mental health promotion in the European Union countries. The article is also aimed at adumbrating standards and directions in mental health protection. It also sets out to present guidelines for helping people with mental illnesses that are based on the results of our research. This work presents selected results of a study which was carried out within the "Diagnosing the aid and social support system for people with mental illnesses in the Mazovia Province" research project. The project was co-financed from the resources of the Human Capital Operational Programme (as part of European Union's European Social Fund).
Keywords: mental health protection, health policy towards people with mental illnesses